2013
DOI: 10.3389/fpsyg.2013.00003
|View full text |Cite
|
Sign up to set email alerts
|

Taijin Kyofusho and Social Anxiety and Their Clinical Relevance in Indonesia and Switzerland

Abstract: Background: Taijin Kyofusho Scale (TKS) is an interpersonal fear to offend others and is defined by Diagnostic and Statistical Manual of Mental Disorders (DSM-IV) as a culturally bound syndrome that occurs in Japan and Korea. Recently, cases with TKS have also been recognized in other cultures. The present questionnaire study investigated self-report TKS symptoms and social anxiety symptoms, and their clinical relevance in an Indonesian and Swiss sample. It also investigated whether self-construal is associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
43
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(62 citation statements)
references
References 61 publications
1
43
0
3
Order By: Relevance
“…This is because college students are very closely related to performance situations (speaking in front of people, conveying ideas/thoughts, evaluation situations) and situations of social interaction (interacting with new people as well as authoritative figures such as lecturers) which is potentially cause the emergence of social anxiety. From several studies that have been conducted by researchers in previous years (Suryaningrum, 2006(Suryaningrum, , 2016, Hasibuan et al, (2015), and Vriends et al (2013), it showed the same result that social anxiety among Indonesian college students tend to be at high level.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…This is because college students are very closely related to performance situations (speaking in front of people, conveying ideas/thoughts, evaluation situations) and situations of social interaction (interacting with new people as well as authoritative figures such as lecturers) which is potentially cause the emergence of social anxiety. From several studies that have been conducted by researchers in previous years (Suryaningrum, 2006(Suryaningrum, , 2016, Hasibuan et al, (2015), and Vriends et al (2013), it showed the same result that social anxiety among Indonesian college students tend to be at high level.…”
Section: Discussionmentioning
confidence: 84%
“…In addition, Vriends, Pfaltz, Novianti and Hadiyono (2013) studied Swiss and Indonesian college students from a University in Yogyakarta and they found that Indonesian college students experience more social anxiety than Swiss college students with very significant differences.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The results of research Vriends, Pfaltz, Novianti, &Hadiyono (2013) associated with social anxiety conducted in Indonesia in 2013 obtained data as much as 15.8% of individuals who experience social anxiety. Miers, Blote, Rooij, &Bookhorst (2013) there is an increase of approximately 9.6% of early social anxiety symptoms of adolescence at age 10.…”
Section: Introductionmentioning
confidence: 99%